Data Health Functionality using Hyperledger Fabric Technology (Journal of Information Technology and Digital World, 2023)
A permissioned blockchain infrastructure called Hyperledger Fabric offers a modular architecture, smart contract execution, configurable consensus, membership services, and a representation of roles between the nodes present in the infrastructure. It also provides high rated integrity sharing. Since patient health records are highly confidential, in order to maintain security, this study examines how to communicate medical data with better privacy protection in healthcare. The transfer of health-related data functions using Hyperledger framework improves the storage reliability and security. Furthermore, the healthcare supply chain process can be improved by hyperledger fabric networks by enhancing the visibility and traceability of network interactions. Companies that have accessibility to the ledger on a fabric network can see the same unchangeable data, enforcing responsibility and lowering the possibility of counterfeiting. This study's findings showcase the utilization of blockchain technology to improve the privacy of data sharing and storage in the healthcare sectors.
Keywords: Data fabric; secure data; IoT signal; data mining; data integration; data intelligence